HASAN AL-BANNA THOUGHT ACTUALISATION IN THE ISLAMIC EDUCATION DEVELOPMENT - Mualimul Huda (P3M STAIN Kudus, 2015)
The things of initiating the discourse about the thinking of Islamic Education from the perspective of Hasan al-Banna is a result of thought he was about the concept of Islamic education, namely to return it to the Qur’an and the hadiths. An extensive microinsurance conducted a type of qualitative research and library research. With the method and approach such technique is expected can be known exactly how the Islamic education from the perspective of Hasan al-Banna, and how the relevance of education thought Hasan al-Banna in developing the Islamic education in the future. From the research that has been done, it is known that the perspective of Islamic Education according to Hasan al-Banna on the fact is concerned with the overall aspects of the authors mentioned above and want to realize all kinds of education as a whole. Because of Islamic education is education man completely; the mind and heart, spiritual and physical, morals and skills. Hasan al-Banna formulate Islamic Education built on the religion of Islam that originate from: First, the Qur’an and tafsirnya, which prioritizes the misinterpretation of Salafist insurrection. Second, the United States of the Sunnah with keauntentikan and syarahnya with keep on the priests of the hadiths is trusted.